The New Keynesian Phillips Curve in an Inflation Targeting Country: The Case of Turkey - Giray Gozgor (International Journal of Economic Sciences and Applied Research, 2013)
The possible short-run trade-off between the inflation (gap) and the output (gap) remains a critical policy issue for any emerging economy; particularly when an implicit or an explicit inflation targeting monetary policy is considered. The New Keynesian Phillips Curve (NKPC) has recently set up a framework on the trade-off between the inflation (gap) and the difference between the actual output and potential (efficient) output under the assumption of real wage rigidities. In this paper, we estimate the NKPC based on this framework for the Turkish economy over a period of implicit and explicit inflation targeting monetary policy. The results from Generalized Methods of Moments (GMM) estimation suggest that empirical findings are consistent with the theoretical background and the parameter restrictions are satisfied.
Keywords: E24; E31; C52; 330; New Keynesian Phillips Curve; Real Wage Rigidity; Short-run Trade-off; Turkey; Developing Economies; New-Keynesian Phillips Curve; Reallohn; Lohnrigidität; Geldpolitik; Inflationssteuerung; Schätzung; Türkei